Intrusion of maxillary molar using mini-implants: A clinical report and follow-up at 5 years - Pinzan-Vercelino, Célia Regina Maio; Bramante, Fausto Silva; de Araújo Gurgel, Júlio; Vergani, Eliane Cristina Carrera Eleres; de Souza Gregório, Rosyane (Elsevier, 2017)
This clinical report describes a straightforward alternative treatment for adult patients with extruded maxillary molars, who are reluctant to use fixed appliances and complex mechanics. The maxillary molar supereruption of a 57-year-old woman was treated using buttons bonded to the buccal and palatal surfaces of the molars, 2 mini-implants, and elastomeric chains. The intrusion was achieved in 5 months. The treatment stability was observed for 5 years after treatment.